Amanita lacerosquamosa, a new species of Amanita sect. Validae from southwestern China - Zhang, Kai-Ping; Zhang, Yi-Zhe; Sun, Cheng-Ye; Zhang, Hong-Shun; Lu, Jun-Jia; Si, Jing; Li, Hai-Jiao (Phytotaxa, 2020)
Amanita lacerosquamosa, a new species of Amanita sect. Validae, is described from southwestern China based on morphological and phylogenetic evidence. The new species is characterized by its medium-sized basidioma, greyish brown, brown to dark brown pileus with brownish grey to greyish brown, verrucose, patchy and sometimes subpyramidal remnants of the universal veil, upper-middle to lower-middle annulus on stipe with snakeskin shaped, floccose, grey to light brown squamules above the annulus, and amyloid, globose, subglobose to broadly ellipsoid basidiospores 6−7.5 × 5−7 μm.